Silent Actors Under States of Exception: Ayacucho during the Internal Armed Conflict in Peru (1980-2000) - Gamarra Carrillo, Jefrey Antonio (2023)
Under internal armed conflicts there is a group of social actors whose performing behaviors do not correspond to neither of the sides in conflict. These actors are neither civil population trapped at the middle of violence nor those compromised with any of the sides. It is state officials charged to accomplish administrative tasks, for example those assigned to education on disputed territories. This paper seeks to explore the notion of silent social actor in terms of its behavior and to draw the attention of the international community concerned about the silent actor on conflicts. This research is focused on a public university in Ayacucho, Peru, during the internal armed conflict (1980-2000) at the end of the last century. The research uses a methodology for studying memory of witnesses of this period and the reflexivity approach in Anthropology. This work proposes using the category of silent social actor characterized by the exercise of a restricted agency but subject to constant pressure from the contenders faced in the conflict.